Functionality of the learning platform and its effect on the satisfaction of students in the online teaching environment - Omar Chamorro-Atalaya; Guillermo Morales-Romero; César León-Velarde; Lourdes Quevedo-Sánchez; Yurfa Medina-Bedón; Abel Tasayco-Jala; Maritte Fierro-Bravo (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
The objective of this article is to identify the results of the functionality of the learning platform and its effect on the satisfaction of mechanical and electrical engineering students, the results will serve as a basis for the continuous improvement of teaching-learning online from the higher institution. The research findings indicate that the indicators that present a better perception regarding the functionality of the learning platform are related to the design and ease of navigation. However, 21.4% of the students are not entirely satisfied with its functionality due to the technical problems presented when downloading the study material. According to the results, we can point out that the functionality of the learning platform generates an effect of 70.87% on student satisfaction, the relationship was validated through the Chi-square test, in which it is determined that the indicators that generate a Greater satisfaction in students refers to the design, availability (connectivity) and the ease of communication and interaction with the teacher and classmates.